2020
DOI: 10.18291/njwls.v10i2.120819
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Perceptions of Older Workers and Implications for Job Retention

Abstract: Older workers’ opportunities for late careers are influenced by employer attitudes and willingness. Nordic managers seem unwilling to hire and retain older persons. In this article, we explore Norwegian workplace perceptions of older workers and the way they are positioned at the workplace.We base this article on qualitative interviews with managers and both union and HR-representatives from 19 companies. Previous research has linked this unwillingness to stereotypes and ageism among employers. We find that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…When comparing ISCO group 1–4 (mainly seated work) with ISCO group 5–9 (mainly physical work), employees from ISCO group 5–9 were significantly less likely to report their managers to have four out of the five positive attitudes, the exception being, “Older workers are easy to cooperate with”. These findings support previous studies indicating that the attitudes towards older workers varies across occupational groups [ 19 , 21 , 22 , 23 , 24 , 27 ] and that managers in white-collar jobs may have less negative attitudes towards older workers [ 21 , 22 ]. Surprisingly, the results showed that respondents from ISCO groups 5–9 were also significantly less likely to believe their managers to have three of the five directly negative perceptions of older workers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…When comparing ISCO group 1–4 (mainly seated work) with ISCO group 5–9 (mainly physical work), employees from ISCO group 5–9 were significantly less likely to report their managers to have four out of the five positive attitudes, the exception being, “Older workers are easy to cooperate with”. These findings support previous studies indicating that the attitudes towards older workers varies across occupational groups [ 19 , 21 , 22 , 23 , 24 , 27 ] and that managers in white-collar jobs may have less negative attitudes towards older workers [ 21 , 22 ]. Surprisingly, the results showed that respondents from ISCO groups 5–9 were also significantly less likely to believe their managers to have three of the five directly negative perceptions of older workers.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, findings indicate that older managers [ 13 , 21 , 22 , 23 ] and managers that are in more frequent contact with older workers [ 13 ] hold more positive attitudes towards older workers. A recent study found that concrete experiences with older workers influenced the managers′ perceptions of older workers [ 24 ], indicating that it is not enough merely to have frequent contact with older workers to develop more positive attitudes towards them; the concrete experiences have to be positive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, we seek to present rich insights into employers' justifications about employing older workers. Nevertheless, the current study is important and innovative, since it reveals not only the justifications used by employers to explain that they do not employ older workers (Frøyland and Terjesen, 2020), but also the perceived “objective reasons” used by employers. As we demonstrated with our findings and analysis, employers' attitudes and abilities with respect to recruiting older workers are not always objective.…”
Section: Discussionmentioning
confidence: 95%
“…Some previous studies investigated age-based bias and examined situations in which older workers encountered discrimination, for example in hiring, promotion and layoffs (Axelrad et al, 2013;Mong and Roscigno, 2010). While there is a general agreement that such discrimination poses a social problem from a normative as well as a practical perspective (Macnicol, 2005(Macnicol, , 2006, less is known about employers' justifications for these practices (Frøyland and Terjesen, 2020), which may explain some of the barriers faced by older workers (Axelrad, 2021).…”
Section: Introductionmentioning
confidence: 99%